2002
DOI: 10.1046/j.1523-1739.2002.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Directing Research to Reduce the Impacts of Nonindigenous Species

Abstract: Management of nonindigenous species is a crucial aspect of maintaining native biodiversity and normal ecosystem functions. We attempt to guide researchers in developing projects that will be of use to conservation practitioners, tangibly improving applied conservation measures. We advocate a directed approach for conservation research to aid in prioritizing nonindigenous species for intervention by resource managers. This approach includes outlining what needs to be known to make such relative judgments about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
314
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(323 citation statements)
references
References 88 publications
1
314
1
7
Order By: Relevance
“…However, we require forecasting methods that can be applied to new and emerging invaders, for example, where a new species has just arrived or is known to be spreading, or indeed potential new invasive species from known donor region 'hotspots' such as the Ponto-Caspian region (Ricciardi and MacIsaac 2000). Invasive species are characteristically more able to rapidly and efficiently utilise resources than native species (Vitousek 1990;Strayer et al 1999;Byers et al 2002;Funk and Vitousek 2007;Johnson et al 2008;Weis 2010;Morrison and Hay 2011;Chapple et al 2012) and thus resources, such as native prey species, are vulnerable to potentially severe declines or extinctions (Clavero and Garcia-Berthou 2005;Snyder and Evans 2006;Salo et al 2007;Cucherousset and Olden 2011;Roy et al 2012). Indeed, difference in resource use is a major tenet of 28 of 29 invasion hypotheses identified by Catford et al (2009).…”
Section: Species Traits Comparisons and The Utility Of Functional Resmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we require forecasting methods that can be applied to new and emerging invaders, for example, where a new species has just arrived or is known to be spreading, or indeed potential new invasive species from known donor region 'hotspots' such as the Ponto-Caspian region (Ricciardi and MacIsaac 2000). Invasive species are characteristically more able to rapidly and efficiently utilise resources than native species (Vitousek 1990;Strayer et al 1999;Byers et al 2002;Funk and Vitousek 2007;Johnson et al 2008;Weis 2010;Morrison and Hay 2011;Chapple et al 2012) and thus resources, such as native prey species, are vulnerable to potentially severe declines or extinctions (Clavero and Garcia-Berthou 2005;Snyder and Evans 2006;Salo et al 2007;Cucherousset and Olden 2011;Roy et al 2012). Indeed, difference in resource use is a major tenet of 28 of 29 invasion hypotheses identified by Catford et al (2009).…”
Section: Species Traits Comparisons and The Utility Of Functional Resmentioning
confidence: 99%
“…This may, in part, be due to a lack of rigour in defining these hypotheses (Heger et al 2013) and lack of focus on demographic processes. These two major challenges need to be simultaneously addressed to advance the fundamental science of invasion ecology and to provide practical methodologies that prioritize and mitigate invasion threats by, for example, refining risk assessment protocols (Ricciardi and Rasmussen 1998;Parker et al 1999;Byers et al 2002;Andersen et al 2004;Kumschick et al 2012;Leung et al 2012) and managing biological communities to provide maximum biotic resistance (Taylor and Duggan 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The assumption made in this research is that the clustering of non-native occurrence records near ports is due to the likelihood that these species are introduced via commercial shipping into ports , at least in primary transport, and secondary spread will occur via intraregional transport mechanisms (Wasson et al, 2001). Given the extra steps involved and time lag to spread from the initial point of introduction (Crooks & Soulé, 1999;Byers et al, 2002), densities are expected to be highest close to ports in near term post invasion timescales with densities at distances scaling with time since invasion. In this study, results show that C. maenas, which has the longest invasion history, has been able to spread the farthest from ports, and C. japonica, the species with the shortest invasion history, has spread the least.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of these publications were careful to note that these effects were merely a possibility, they had a snowball effect whereby subsequent literature used them as proof of the putative impacts. This problem clearly reflects the fact that "… because positive results are more likely to be submitted and published, the invasion literature may be biased toward demonstrating that nonindigenous species have large ecological impacts" (Byers et al 2002). Furthermore, the same bias seems to permeate grant submissions, conference reports, newspaper and magazine articles, consultant reports, thesis dissertations, book chapters, web pages, etc., where the importance of impacts is exaggerated in the hopes of getting Preface xi funding or recognition.…”
Section: Japanmentioning
confidence: 99%
“…Numerous reports have shown that the same introduced species can have very dissimilar effects in different habitats, and even within the same habitat, with changing environmental conditions (Byers et al 2002 (Boltovskoy and Correa 2015). This approach hampers objective analyses and does little to advance our understanding of how this species interacts with its new environment.…”
Section: Japanmentioning
confidence: 99%